Corrosion Behavior of Heat Treated Nanocrystalline Co Ni Fe Coating on Stainless Steel / Koay Mei Hyie...[et al.] - Koay, Mei Hyie; Salleh, Zuraidah; Mardziah, C.M.; Mohd Masdek, Nik Rozlin Nik; Resali, Nor Azrina (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Corrosion is an essential environmental phenomenon in industry that can deteriorate the performance of steel and shorten the lifetime of steel. The failure due to corrosion can cause leakage, fracture, contamination of corroded elements to the product or equipment having the corroded steel parts. To overcome the corrosion problem, nanocrystalline coating has been proposed to improve the corrosion resistance of steel. In this investigation, nanocrystalline Co-Ni-Fe was used to protect the stainless steel from sodium chloride environment. Co-Ni-Fe has been identified as a potential candidate in corrosion resistant coating. This material is recognized as a green material because it is not toxic and hazardous to environment. In this study, nanocrystalline Co-Ni-Fe having less than 30 nm crystallite size was developed by low cost electrodeposition method. The coating electrodeposition was carried out at pH 1 and current density of 0.143 A/cm2. The synthesized Co-Ni-Fe coated stainless steel was heat treated at 700C in different types of gas conditions. This paper focused on comparison between the samples with and without heat treatment. Although there is no phase changed during the heat treatment as proven in XRD analysis, nanocrystalline Co-Ni-Fe heated using mixed gases showed the tendency to form the dendritic structure. In the presence of hydrogen and argon mixing gases in heating atmosphere, the sample revealed higher oxygen content of 5.34 wt% and exhibited the highest corrosion rate in sodium solution. Anyway, the coating still protected the stainless steel from corrosion after exposed to 24 hours in salt fog test as compared to the pure stainless steel which was corroded at the same test. In conclusion, the heat treatment applied on the coating sample is believed to produce dense coating and thus enhance the corrosion resistance of the coated steel.